2010
DOI: 10.1177/0148607110362532
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Fish Oil–Enriched Parenteral Nutrition Regimen on Postoperative Patients Undergoing Major Abdominal Surgery

Abstract: Based on the meta-analysis, fish oil-supplemented parenteral nutrition was safe, improved clinical outcomes, and altered the fatty acid pattern as well as leukotriene synthesis. More laboratory parameters should be considered in future meta-analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
18

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 53 publications
4
85
0
18
Order By: Relevance
“…Administration of n-3 long-chain polyunsaturated fatty acids (LC-PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) to adults who undergo surgical trauma has resulted in decreased inflammatory cytokines [7], reduced risk of developing infections and shorter stays in intensive care unit (ICU) [9]. Such possible beneficial effects have been scarcely investigated in neonates who present a high susceptibility and risk of death; therefore, it is relevant to evaluate new strategies to improve their clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of n-3 long-chain polyunsaturated fatty acids (LC-PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) to adults who undergo surgical trauma has resulted in decreased inflammatory cytokines [7], reduced risk of developing infections and shorter stays in intensive care unit (ICU) [9]. Such possible beneficial effects have been scarcely investigated in neonates who present a high susceptibility and risk of death; therefore, it is relevant to evaluate new strategies to improve their clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The current review pooled data from 17 studies and showed like Chen et al [17] a significant reduction in the infection complications rate, HLOS and ICU stay, liver profile (AST), and lipid fatty acid patterns (increase of EPA and DHA) when PN was enriched with FO. In our study, further improvement was noted in the results of immune function (CD 4+ /CD 8+ ) and inflammatory response (decrease of IL-6 and TNF-α).…”
Section: Discussionmentioning
confidence: 87%
“…However, there are studies demonstrating that administration of FO (0.2 g/kg per day) after surgical stress is not immunosuppressive, but increases production of IFN-γ, TNF-α, and IL-2 [16]. Previous meta-analysis demonstrated that parenteral nutrition enriched with FO have proven to be well tolerated, in terms of clinical and metabolic outcomes [17][18][19]. However, the studies included in these meta-analyses are very heterogeneous in their interventions and subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated fatty acids as precursors of prostaglandins, are important components of cell membranes, which maintain the fluidity of cell membranes, and participate in the regulation of cellular and biochemical responses [7]. Fish oil/kg body weight/day (0.2 g) in addition to TPN has been recommended to be taken by gastrointestinal tumor patients after surgery, for reduction of inflammatory response syndrome and post-operative recovery, on the basis of the fact that ω-3 unsaturated fatty acids inhibit the formation of pro-inflammatory factors (IL-6 and TNF-a), increase the synthesis of antiinflammatory factor IL-10, improve immune function and eliminate excessive inflammation [8,9].…”
Section: Discussionmentioning
confidence: 99%